The influence of cyberization on folk religion: A case study of Chinese online religious group - Yuhang Zhang (SIMULACRA: JURNAL SOSIOLOGI, 2021)
Religious cyberization is a new way of dissemination and development of traditional offline religions. In the process of cyberization, all aspects of religions are likely to be affected by the new Internet environment. Taking a Chinese online religious group as Internet field, this article analyzes the influence of cyberization on belief system, religious authority and religious experience of folk religion, and makes a preliminary exploration of its causes in combination with the characteristics of Internet and folk religion. This study mainly adopted the method of participant observation, and conducted online and offline interviews with participants when necessary. In addition, the researcher also analyzed documents, audio and other files uploaded in the online group. In the case discussed in this article, compared with officially recognized religions in China, folk religion seems to be more adapted to the opportunities and challenges brought by the new territory of the Internet due to its unique diffuseness and inclusiveness.